Separate Submission of Standard Lymphadenectomy in 6 Packets Versus En Bloc Lymphadenectomy in Bladder Cancer - Ather, M Hammad; Alam, Zaheer; Jamshaid, Anila; Siddiqui, Khurram M; Sulaiman, M Nasir (Urology Journal, 2008)
Introduction: Our aim was to evaluate detection of nodal metastasis during radical cystectomy with standard pelvic lymph node dissection versus en bloc lymphadenectomy for the treatment of bladder cancer. Materials and Methods: Hospital records of a total of 77 patients with radical cystectomy and either standard pelvic lymph node dissection or en bloc lymphadenectomy were reviewed. Nodal dissection specimens during standard lymphadenectomy were sent for pathology examination in 6 separate containers marked as external iliac, internal iliac, and obturator groups from both sides. En bloc dissection specimens were sent in 2 containers marked as the right and the left pelvic nodes. Clinical and pathological findings of these two groups were compared in terms of the number of dissected lymph nodes, number of nodes with metastasis, lymph node density, and clinical outcomes. Results: There were 34 patients with standard lymph node dissection and 43 with en bloc lymphadenectomy (anterior pelvic exenteration). Age, sex, duration of the disease, number of transurethral resections prior to cystectomy, pathological grade at cystectomy, and stage of the primary tumor were comparable in the two groups of patients. The median numbers of nodes removed per patient were 15.5 (range, 4 to 48) and 7.0 (range, 1 to 24) in those with standard and en bloc lymphadenectomy, respectively (P < .001). Nodal involvement was detected in 10 (29.4%) and 9 (20.9%) patients, respectively (P = .43). Conclusion: Although nodal involvement was not significantly different between the two groups, standard lymphadenectomy submitted in 6 different containers significantly improved the nodal yield over en bloc resection. Obturator nodes were the most commonly involved nodes in our study.